Analysis of genetic diversity and structure across a wide range of germplasm reveals genetic relationships among seventeen species of Malus Mill. native to China - Yuan GAO; Da-jiang WANG; Kun WANG; Pei-hua CONG; Lian-wen LI; Ji-cheng PIAO (Journal of Integrative Agriculture, 2021)
China is a center of diversity for Malus Mill. with 27 native species including 21 wild species and six domesticated species. We applied a set of 19 simple sequence repeat markers to genotype 798 accessions of 17 species (12 wild species and five cultivated species) of Malus originating from 14 provinces in China. A total of 500 alleles were detected. Diversity statistics indicated a high level of genetic variation as quantified by the average values of the effective allele number (Ne), expected heterozygosity (He), and Shannon’s Information Index (I) (10.309, 0.886, and 2.545, respectively). Malus sieversii (MSR; He=0.814, I=2.041, Ne=6.054), M. baccata (MBB; He=0.848, I=2.350, Ne=8.652), M. toringoides (MTH; He=0.663, I=1.355, Ne=3.332), and M. hupehensis (MHR; He=0.539, I=0.912, Ne=0.579) showed a higher level of genetic diversity in this study than the previous studies. MSR and MBB contributed to the origin and evolution of some accessions of M. domestica subsp. chinensis (MDC). However, other accessions of MDC showed a closer genetic distance with MBB and cultivated species, especially M. robusta (MRB), M. asiatica (MAN), and M. prunifolia (MPB). Not all accessions of MDC were descended from MSR in Xinjiang Uygur Autonomous Region of China. This research provides novel insights into the genetic relationships of Malus native to China, which will be useful for genetic association studies, germplasm conservation, and breeding programs.